Farmers' attitudes and knowledge level on organic farming in Region I and Cordillera Administrative Region - Pastor, Floramante C. (Transactions of the National Academy of Science and Technology, 2011)
This study mainly focused on the assessment of attitudes and level of knowledge of farmers towards organic farming (OF) and the contributory factors that are assumed to affect these. Two groups of respondents were interviewed: a) NOF or farmers who have not tried OF; and 2) TOF or farmers who have tried OF, either partially or discontinued. T-test was used to analyze the significant difference of NOF and TOF as to attitudes and knowledge. Person correlation was used to determine which of the socio-demographic characteristics significantly affect the attitudes and knowledge respondents towards OF. Results showed that most of the farmers in both regions are aware of OF. However, there are TOF in Region 1 who re unaware. They are practicing organic techniques but are unaware that such is organic in nature. Statistics showed that NOF and TOF respondents are significantly different with their attitudes on some attributes of OF. Both groups in two regions are uncertain of the negative and agreeable of the positive attributes of OF but TOF respondents are more optimistic. Socio-demographics have no effect on the attitudes of both NOF and TOF. Notable demographic factors that have influences on technical knowledge and some aspect of OF are religion, educational attainment, ethnicity, number of years in farming, annual income and farm size. Notable reasons for non-adoption/discontinuance of OF are economics impact during conversion period like low yield, slow effect, laborious, no sustained government support and low technical knowledge on OF. These can be some possible entry points for promotional activities on organic farming in the country.